A food system transformation pathway reconciles 1.5 °C global warming with improved health, environment and social inclusion - Bodirsky, Benjamin Leon; Beier, Felicitas; Humpenöder, Florian; Leip, Debbora; Crawford, Michael S.; Chen, David Meng-Chuen; von Jeetze, Patrick; Springmann, Marco; Soergel, Bjoern; Nicholls, Zebedee; Strefler, Jessica; Lewis, Jared; et al. (Springer, 2025)
The improvement of the global food system requires a thorough understanding of how specific measures may contribute to the system’s transformation. Here we apply a global food and land system modelling framework to quantify the impact of 23 food system measures on 15 outcome indicators related to public health, the environment, social inclusion and the economy, up to 2050. While all individual measures come with trade-offs, their combination can reduce trade-offs and enhance co-benefits. We estimate that combining all food system measures may reduce yearly mortality by 182 million life years and almost halves nitrogen surplus while offsetting negative effects of environmental protection measures on absolute poverty. Through joint efforts, including measures outside the food system, the 1.5 °C climate target can be achieved.